Primary Quadriceps Tendon Suture Anchor Repair: Case Presentation and Surgical Technique. (August 2022) - Dankert, John F.; Mehta, Devan D.; Mahure, Siddharth A.; Mojica, Edward S.; Lowe, Dylan T.; Leucht, Philipp; Jazrawi, Laith
Summary: This case presentation described a technique for repairing an acute quadriceps tendon rupture with suture anchors. The patient was a 51-year-old man who sustained an acute quadriceps tendon rupture after a fall. We used a midline incision over the quadriceps tendon and muscle. The tendon was found to be completely avulsed from the superior border of the patella. Three suture anchors were used to re-approximate the quadriceps tendon to the patella and additional sutures were used to repair the medial and lateral patellar retinacula. The patient had excellent range of motion at his 6-week follow-up appointment after the procedure.